Analisis Aplikasi Kopi Kenangan Berperdoman pada Prinsip Interaksi Manusia dan Komputer - Putra, Theofilus Dewa; Wahyuningsih, Yulia (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
Indonesian memorable coffee application is an application that helps consumers to order a drink without having to queue or leave the house. Human and computer interaction is a multi-disciplinary field that focuses on computer technology design, especially on the interaction between humans as users and computers/applications. Through this interaction, developers are required to pay attention to several things such as functionality, user experience, and interface design so that users are comfortable using the application. The analysis was conducted to see how far the guidelines on the principles of human and computer interaction were applied in the Indonesian coffee memories application. There are several aspects evaluated such as human aspects, technological aspects, ergonomic aspects and usability aspects. The results show that the application has fulfilled the aspects of human and computer interaction.